Pesan Dakwah Dalam Film Ustad Milenial Terhadap Masyarakat Perkotaan - fuad dakwah uinsatu (Hikmah, 2022)
The world of cinema has developed rapidly. Various types of films have been produced, and shown on TV media, Social Media and other applications such as WeTv, Iflix, etc. With the development of the film world, it can also be used as a medium for preaching. With da'wah through films whose message can be taken through behavior, his words can also be used as changes for the better. As in this Ustad Millenial film which describes everyday life. In this film tells about love, life, and also about religion in everyday life. This study aims to determine the message of da'wah in the film Ustad Millenial. The author is interested in studying this research because this film is interesting to serve as an example of da'wah in film media. The methodology that the author uses is a qualitative research methodology, with the method of da’wah bil lisan. The research data was obtained from the observation of the Ustad Millenial film epsd 1-20 and then took a scene that contained the message of his da'wah.